Influence of Workload and Work Environment on Employee Performance with Work Motivation as a Mediating Variable at PT MAK - Nilla Ayunda Ambar Wigati; Sandi Supaya; Yusmar Ardhi Hidayat (Politeknik Negeri Semarang, 2025)
This study is grounded in the critical role of human resource management within the dynamic maritime logistics industry, where workload and work environment are key factors influencing employee motivation and performance. The objective of this research is to examine the influence of workload and work environment on employee performance, with work motivation serving as a mediating variable, conducted at PT MAK. A quantitative research design was employed, utilizing a survey method involving 64 employees as respondents. Data analysis included validity and reliability testing, classical assumption testing, path analysis, and hypothesis testing. The findings reveal that both workload and work environment have a significant effect on work motivation. Furthermore, the work environment has a direct and significant impact on employee performance, whereas workload does not show a direct effect. However, work motivation is proven to mediate the relationship between both workload and work environment on employee performance. This study offers valuable contributions by providing practical insights for organizations, particularly in the maritime logistics sector, emphasizing the importance of effective workload management and a supportive work environment in enhancing employee motivation and performance. The results may serve as a reference for the formulation of human resource policies aimed at improving operational productivity. Penelitian ini didasarkan pada peran penting manajemen sumber daya manusia dalam industri logistik maritim yang dinamis, di mana beban kerja dan lingkungan kerja merupakan faktor kunci yang memengaruhi motivasi dan kinerja karyawan. Tujuan penelitian ini adalah untuk menguji pengaruh beban kerja dan lingkungan kerja terhadap kinerja karyawan, dengan motivasi kerja sebagai variabel mediasi, yang dilakukan di PT MAK. Desain penelitian kuantitatif digunakan dengan metode survei yang melibatkan 64 karyawan sebagai responden. Analisis data meliputi uji validitas dan reliabilitas, uji asumsi klasik, analisis jalur, dan uji hipotesis. Temuan penelitian menunjukkan bahwa beban kerja dan lingkungan kerja memiliki pengaruh yang signifikan terhadap motivasi kerja. Lebih lanjut, lingkungan kerja memiliki pengaruh langsung dan signifikan terhadap kinerja karyawan, sementara beban kerja tidak menunjukkan pengaruh langsung. Namun, motivasi kerja terbukti memediasi hubungan antara beban kerja dan lingkungan kerja terhadap kinerja karyawan. Studi ini menawarkan kontribusi berharga dengan memberikan wawasan praktis bagi organisasi, khususnya di sektor logistik maritim, dengan menekankan pentingnya manajemen beban kerja yang efektif dan lingkungan kerja yang suportif dalam meningkatkan motivasi dan kinerja karyawan. Hasil penelitian ini dapat menjadi referensi dalam perumusan kebijakan sumber daya manusia yang bertujuan untuk meningkatkan produktivitas operasional.